2009
DOI: 10.1080/15427520903304269
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Response to High Water Tables and Intermittent Flooding

Abstract: Sugarcane production has engendered environmental concerns of nutrient transfer and subsidence of organic soils. Retaining water on fields would ameliorate these environmental issues. The objective of this research was to document the growth of sugarcane subjected to various high water-table treatments. Two experiments were conducted across two years using three sugarcane cultivars grown outdoors in large pots. Key aspects were to examine the timing of when water-table treatments were imposed and the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…An interesting alternative proposed for employing flood-prone lands in the tropics is the cultivation of sugarcane, which was reported as a flooding-tolerant plant that may even benefit from short flooding periods in the form of increased sugar yields (Glaz and Gilbert, 2006; Ray et al, 2010). The genetic potential of sugarcane was demonstrated in a multi-harvest field-test where family clones of sugarcane, valued for their sugar or biomass yields, were able to retain productivity of both in the face of intermittent flooding (Viator et al, 2012).…”
Section: Biotechnological Success and Explorationsmentioning
confidence: 99%
“…An interesting alternative proposed for employing flood-prone lands in the tropics is the cultivation of sugarcane, which was reported as a flooding-tolerant plant that may even benefit from short flooding periods in the form of increased sugar yields (Glaz and Gilbert, 2006; Ray et al, 2010). The genetic potential of sugarcane was demonstrated in a multi-harvest field-test where family clones of sugarcane, valued for their sugar or biomass yields, were able to retain productivity of both in the face of intermittent flooding (Viator et al, 2012).…”
Section: Biotechnological Success and Explorationsmentioning
confidence: 99%
“…hybrid which showed an increase in dry biomass in response to flooding. Continuous flooding is often deleterious to sugarcane growth [117], but because it is typically cultivated in wet tropical regions, it is important to develop varieties that are productive under flooded conditions. Several of the focal biomass crops have not been the subject of study related to flooding tolerance (i.e., "N/A" in Table 2), but this lack of evidence should not be interpreted as flood sensitivity for these taxa.…”
Section: C4 Highmentioning
confidence: 99%
“…Suggesting that sugarcane genotypes differ in root growth due to water availability, Sakaigaichi et al (2007) reported that in response to drought, sugarcane roots of two sugarcane genotypes differed in shoot–root amounts and in the percentage of roots with vertical growth. Ray et al (2009) found that increasingly shallow water tables and flooding reduced the rooting depth, but they did not identify these effects on young plants or on root biomass. The purpose of this study was to determine the effects of the time of flood onset and flood duration on leaf, stalk, and root biomass accretion of recently planted sugarcane.…”
mentioning
confidence: 93%
“…Generally, during these periods, the sugarcane crop is in a rapid growth phase and has already covered the space between rows. Ray et al (2009) found that the longer the flood duration, the greater was the yield loss of sugarcane. In Florida, research has focused on yield responses to shallow water tables and flooding during this period of rapid growth.…”
mentioning
confidence: 99%